2013
DOI: 10.1021/nl402384r
|View full text |Cite
|
Sign up to set email alerts
|

Nanometallic Glasses: Size Reduction Brings Ductility, Surface State Drives Its Extent

Abstract: Figure S1: Average Young's moduli for FIB and EP samples across ten independent specimens (five of each type). EP samples show a slightly lower modulus, but it is within one standard deviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
100
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 45 publications
3
100
0
Order By: Relevance
“…Stress-strain data in these samples show distinct work hardening to $25% true strain and permanent plastic deformation upon unloading past the elastic limit. 9 Similar plasticity and necking have been reported for electroplated (EP) NiP MGs with diameters of 100 nm and below that were fabricated with and without the use of focused ion beam (FIB), 10 as well as for melt-spinned CuZr MGs with diameters 70-120 nm fabricated with FIB. 11 Necking and strain hardening are typical for crystalline metals and metal alloys, whose plastic flow is enabled by the motion and interactions of dislocations but are anomalous for amorphous metals.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Stress-strain data in these samples show distinct work hardening to $25% true strain and permanent plastic deformation upon unloading past the elastic limit. 9 Similar plasticity and necking have been reported for electroplated (EP) NiP MGs with diameters of 100 nm and below that were fabricated with and without the use of focused ion beam (FIB), 10 as well as for melt-spinned CuZr MGs with diameters 70-120 nm fabricated with FIB. 11 Necking and strain hardening are typical for crystalline metals and metal alloys, whose plastic flow is enabled by the motion and interactions of dislocations but are anomalous for amorphous metals.…”
supporting
confidence: 53%
“…Recent in-situ observations of a brittle-to-ductile transition emergent in nanometer-sized metallic glasses under tension suggest a mechanism for plasticity not involving shear bands. [8][9][10][11] In one such work, Jang et al demonstrated that Zr 35 Ti 30 Co 6 Be 29 metallic glass nano-cylinders underwent a transition from catastrophic shear banding in samples with diameters greater than 100 nm to a ductile necking-to-shearbanding deformation prior to failure in thinner samples. Stress-strain data in these samples show distinct work hardening to $25% true strain and permanent plastic deformation upon unloading past the elastic limit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain more accurate results, instead of using the raw data of the measured displacement signal, frames from the in-situ SEM videos were examined to determine the actual displacement. This technique allows for more reliable strain data and has been used successfully in many publications [5][6][7] . The InSEM system (Nanomechanics, Inc.) used has a load resolution of 3 nN and a displacement resolution of 0.0002 nm.…”
Section: Tensile Testingmentioning
confidence: 99%
“…The "smaller is more ductile or deformable" size effect frequently observed in metallic glass nanopillars has predominantly been rationalized by the high surface-to-volume ratio in nanopillar samples, which increases the energetic cost of forming and propagating a shear band compared to homogeneous deformation [6,8,9,[48][49][50]. For a sample of dimension, , the energy required for a crack-like shear band to propagate scales with the sample cross-sectional area, or while the energy required to deform a sample in a homogeneous way scales with the sample volume, or .…”
mentioning
confidence: 99%